The primary phase part in microstructure formation of in-situ eutectic composite of LaB₆-ZrB₂ - Ereshchenko, A.A.; Paderno, Yu.B.; Filippov, V.B.; Paderno, V.N. (Functional Materials, 2005)
The crystal orientation relationships (COR) of LaB₆-ZrB₂ eutectic phase produced by directional solidification (DS) correspond to non-optimum coherency conditions of phase boundaries. Another peculiar feature of this eutectic is the dominant role of primary low temperature phase (LaB₆) in the cooperative eutectic growth. As a rule, it is just the high-temperature phase that plays a leading role in the crystallization and promotes heterogeneous nucleation of the second phase. In contrast, in LaB₆-ZrB₂ eutectic system, the high-temperature ZrB₂ whiskers start to grow on (100) faces of low-temperature LaB₆ phase. A possibility of discrete changes in growth direction of the composite regular structure up to 90⁰ has been revealed. It is suggested that all above mentioned features are defined mainly by the nucleation processes during the eutectic co-crystallization process, rather than by the ordinary fundamental criteria of interface surface energy minimization that occurs due to the semi-coherent habit facets formation. Установлено, что кристаллические ориентационные соотношения фаз эвтектики LaB₆-ZrB₂, полученной методом направленной кристаллизации, соответствуют не самым выгодным условиям когерентности межфазных границ. Особенностью этой эвтектики является также превалирующая роль матричной, низкотемпературной фазы в процессе кооперативного эвтектического роста. В отличие от обычного случая, когда высокотемпературная фаза играет ведущую роль при эвтектической кристаллизации и является зародышеобразующей для второй фазы, в эвтектической системе LaB₆-ZrB₂ кооперативный эвтектический рост волокон высокотемпературной фазы ZrB₂ начинается на фасетах (100) низкотемпературной фазы LaB₆. Обнаружена способность дискретного изменения направления роста регулярной структуры композита вплоть до 90⁰. Предполагается, что все упомянутые особенности определяются в основном процессами зародышеобразования во время кооперативной эвтектической сокристаллизации, а не привычными фундаментальными критериями минимизации энергии поверхности межфазных границ за счет формирования их полукогерентных габитусных поверхностей. Встановлено, що кристалiчнi орiєнтацiйнi спiввiдношення фаз евтектики LaB₆-ZrB₂, що отримана методом спрямованої кристалiзацiї, вiдповiдають не найбiльш вигiдним умовам когерентностi мiжфазових меж. Особливiстю цiєї евтектики також є головуюча роль матричної, низькотемпературної фази у процесi кооперативного евтектичного росту. На вiдмiну вiд звичайного випадку, коли високотемпературна фаза є ведучою евтектичну кристалiзацiю i зародкоутворюючою для другої фази, в евтектичнiй системi LaB₆-ZrB₂ кооперативний евтектичний рiст волокнин високотемпературної фази ZrB₂ починається на (100) фасетах низькотемпературної фази LaB₆. Виявлено здатнiсть дискретної змiни напрямку росту регулярної структури композиту на кути до 90⁰. Припускається, що усi згаданi особливостi визначаються в загалом зародкоутворюючими процесами кооперативної евтектичної кристалiзацiї, а не звичними, фундаментальними критерiями мiнiмiзацiї енергiї поверхнi мiжфазових меж за рахунок формування їх напiвкогерентних габiтусних фасет.